Accountability in Humanitarian Action. (3rd December 2021) - Hilhorst, Dorothea; Melis, Samantha; Mena, Rodrigo; van Voorst, Roanne
Abstract: Although a growing number of NGOs are combining humanitarian and development activities, it was long the case that humanitarian action was isolated from discussions and practices in the world of development. The work of saving lives was deemed to be guided solely by the humanitarian principles, and discussions on accountability were rare. In the 1990s, humanitarian standards initiatives arose in recognition that humanitarian organisations were not accountable to affected populations. This article aims to take stock of accountability initiatives and practices in the sector. It builds on accountability theory in distinguishing upward, sideways, and downward accountability, and incorporates formal and informal forms of accountability. It is based on empirical research in Myanmar, Afghanistan, and Sierra Leone. The first part of the article outlines the history of accountability in the humanitarian sector, including an accountability timeline, and discusses current trends in performances around accountability towards displaced people, minorities, and other recipients of aid. It then presents the findings from the three countries. The article concludes by calling attention to the everyday politics of accountability, the widening accountability arena, the differential accountability demands on international and national aid providers, and the crucial importance of sideways accountability to bring accountability to a next level.